Empirical research on the resource‐based view of the firm: an assessment and suggestions for future research - Newbert, Scott L. (Strategic Management Journal, 2007)
The resource‐based view (RBV) is one of the most widely accepted theories of strategic management. However, to date no systematic assessment of the RBV's level of empirical support has been conducted. In response, a sample of RBV‐grounded empirical articles was analyzed from which it was found that the RBV has received only modest support overall and that this support varies considerably with the independent variable and theoretical approach employed. It is therefore suggested that scholars avoid the tendency to test models reflecting early incarnations of the RBV and instead test those that incorporate its more contemporary theoretical extensions. Copyright © 2007 John Wiley & Sons, Ltd.